N - heterocyclic - carbene - catalyzed umpolung of imines - Patra, Atanu; Mukherjee, Subrata; Das, Tamal Kanti; Jain, Shailja; Gonnade, Rajesh Ghanshyam; Biju, Akkattu T. (Angewandte Chemie International Edition, 2017)
N-Heterocyclic carbene (NHC) catalysis has been widely used for the umpolung of aldehydes, and recently for the umpolung of Michael acceptors. Described herein is the umpolung of aldimines catalyzed by NHCs, and the reaction likely proceeds via aza-Breslow intermediates. The NHC-catalyzed intramolecular cyclization of aldimines bearing a Michael acceptor resulted in the formation of biologically important 2-(hetero)aryl indole 3-acetic-acid derivatives in moderate to good yields. The carbene generated from the bicyclic triazolium salt was found to be efficient for this transformation.